Correlation between disease progression and histopathologic criterions of the lip squamous cell carcinoma - Golubović Mileta; Ašanin Bogdan; Jelovac Drago; Petrović Milan; Antunović Marija (Vojnosanitetski Pregled)
Background/Aim.The most common malignancy of the lip is squamous cell carcinoma (SCC). In our population, according to epidemiological data, almost a half of all (45%) SCC of oral mucous tissue spreads over the lower and upper lip. The aim of this study was to estimate prognostic importance of histopathologic characteristics - histologic grade, nuclear grade and tumor size in relation to the appearance of lymph node metastases and relapse in SCC of the lip. Methods. In the retrospective- prospective study 70 cases of lower and upper lip SCC were analyzed. They were diagnosed from 2002 to 2006 in the Clinic of Maxillofacial Surgery, Clinical Center of Montenegro. The data about localization of the carcinomas, histopathologic characteristics and lymph node status were taken from medical files of the patients. The patients were followed up in a 3-year period and the disease relapse or/and metastatic disease appearance were registereds. Results. There was statistically significant difference in tumor size among the patients with and without disease relapse (p = 0.027). Logistic regression analysis showed that the tumor size is a statistically significant factor (R = 0.186; p = 0.011) for the appearance of regional lymph node metastases. Relative risk [exp (B)] for the appearance of regional lymph node metastases in relation to tumor size was 2.807. Conclusion. Histologic and nuclear grade of lip SCC are not prognostic factors for the appearance of the disease relapse and regional lymph node metastases. Tumor size is a predictive factor of the relapse appearance, as well as for lymph node metastases appearance. In clinical practice, tumor size is a factor that classifies patients with lip SCC into the groups of higher and smaller risk of relapse appearance and for lymph node metastases appearance. Our results suggest that, risk for lymph node metastases appearance increases 2.8 times with increasing of the tumor size over 2 cm in diameter.